Acceptability of Lycra arm sleeve in people with sub-acute stroke: patients', carers' and clinicians' perspectives. (March 2023) - Kumar, Praveen; Jones, Robert; Cramp, Mary; Greenwood, Rosemary; White, Paul; Turton, Ailie
Abstract: Background: Previous studies found that the Lycra sleeve has potential to reduce glenohumeral subluxation in people with stroke. The primary aim of this study was to explore the acceptability of the Lycra sleeve from patients', carers' and staff perceptive in the sub-acute phase of stroke. Method: Stroke survivors over 18 years with hemiplegia and muscle strength of ≤ 3 (Medical Research Council scale) shoulder abduction, able to provide informed consent were recruited as soon as they were medically stable. Patients wore the Lycra sleeve for up to 10 h/day for three months. A questionnaire was administered three months post-sleeve application to immediate and delayed groups and healthcare staff. Results: Twenty-seven patients (immediate group (n = 19), delayed group (n = 8)), 23 carers/family-members and 36 healthcare staff (nurses (n = 10), nursing assistants (n = 5), physiotherapists (n = 10), physiotherapy assistants (n = 3) and occupational therapists (n = 8) completed a questionnaire. Several staff reported for more than one patient resulting in up to 37 responses to some questions from nursing staff and 46 responses from therapy staff. Of 27 patients, all found the sleeve to be comfortable. The average time to apply the sleeve was between two and five minutes. The sleeve was reported as acceptable in daily life by patients (96%, n = 24/25), carers/family-members (96%, n = 21/22), by nurses (92%, n = 34/37) and in routine clinical practice by therapists (91%, n = 41/45). Conclusion: Wearing of Lycra sleeve was acceptable for patients during activities of daily living/rehabilitation. However, research is required on the effectiveness of the sleeve before this can be routinely used in clinical practice. Contribution of the Paper: Lycra arm sleeve is comfortable and acceptable by people with acute stroke. Training the staff, patients, family members is easy and feasible. Clinical and cost effectiveness need to be tested in future studies.